Why evolution matters : a jewish view - Rutman, Joel Yehudah (London : Vallentine Mitchell, 2014)
Why Evolution Matters examines the concept of evolution in relation to Judaism, showing that far from something to be avoided within the religion, evolutionary thought deepens an understanding of classic areas of Jewish concern, including free will, moral behavior, suffering, and death. The book presents a novel interpretation of biological evolution in which convergences, self-organization, constraints, and progress are seen as components of the divinely intended world. Why Evolution Matters confronts some major questions that are leveled at the Jewish religion: How can God have created the world when evolution says everything just happened? How can we believe in the truth of Genesis when it conflicts with the facts of evolution? How did we evolve and why does it matter? How and toward what ends should we influence future evolution? The book explains how Genesis and evolutionary cosmology and biology reinforce, rather than contradict, one another. Author Joel Yehudah Rutman, an experienced paediatric neurologist, draws on his own practical experience in a branch of medicine in which our evolutionary past is much in evidence. Why Evolution Matters is a 'must-read' for scientists, religious studies scholars, and anyone with an interest in religion.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Evolution -- Religious aspects; Judaism; RELIGION / Judaism / General; Electronic books